Observation and simulations of an impact on the automotive windshield using the time-dependent dynamic failure criterion. (June 2015) - Kang, Byunghyun; Moon, Sung-wook; Lim, Jaeyoung; Choi, Byoung-Ho
Car accidents involving pedestrians have become an issue of great concern owing to the high fatality and injury rates. To reduce the loss of life during car accidents, the safety of automobiles is evaluated on the basis of standards such as the Federal Motor Vehicle Safety Standards and the European New Car Assessment Program, which provide information about automobile safety to drivers and require manufacturers to produce safe automobiles. Regarding car accidents involving pedestrians, the head injury criterion is used to evaluate pedestrian injury when the head of the pedestrian hits the windshield. In this study, the windshield impact tests were numerically simulated using the Tuler–Butcher criterion as the failure criterion, and considering simulation conditions such as the types of element, the sizes of elements and the parameters of the failure criterion. A parametric study was conducted to investigate the effect of the simulation conditions on the key results such as the head injury criterion, the initial acceleration peak, the displacement and the cracking modes of the windshield, with the purpose of improving the accuracy of the simulation results. The results of the simulations were also compared with those of tests to determine the accuracy of the former.